2007
DOI: 10.1093/ajcn/86.4.1126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early infant feeding practices on infection-specific neonatal mortality: an investigation of the causal links with observational data from rural Ghana

Abstract: This study provides the first epidemiologic evidence of a causal association between early breastfeeding and reduced infection-specific neonatal mortality in young human infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
148
1
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 29 publications
4
148
1
11
Order By: Relevance
“…A study in Ghana reported that 22% of all neonatal deaths could be prevented if all women could initiate breastfeeding within one hour of delivery 11 . The use of pre lacteal feeding was far less (19.1%) compared to the corresponding reported by Roy et al 12 . The corresponding figures were 8% in rural Bangladesh 13 and 71% in urban Bangladesh 14 .…”
Section: Discussionmentioning
confidence: 54%
“…A study in Ghana reported that 22% of all neonatal deaths could be prevented if all women could initiate breastfeeding within one hour of delivery 11 . The use of pre lacteal feeding was far less (19.1%) compared to the corresponding reported by Roy et al 12 . The corresponding figures were 8% in rural Bangladesh 13 and 71% in urban Bangladesh 14 .…”
Section: Discussionmentioning
confidence: 54%
“…Our study results were somewhat similar to studies conducted at Ghana and rural Egypt. 9 Studies have reported that effective counselling is required prior to delivery for early initiation of breast feeding. Regular counselling at different time intervals resulted in sustained breast feeding in later life.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that delay in initiation of breastfeeding after the first hour greatly enhances the chances of neonatal mortality, especially deaths due to infections. 7,16,17 Despite this well-recognized importance of breastfeeding, the worldwide figures are quite dismal. The studies done in different parts of India, too, reflect a poor picture.…”
Section: Discussionmentioning
confidence: 99%